Hydrogen fuel cell in vehicle propulsion: Performance, efficiency, and challenge - Kurnia, J.C. (Springer Singapore, 2019)
This chapter provides comprehensive review on the current development of polymer electrolyte membrane fuel cell (PEMFC) in automotive application to assist further development of hydrogen fuel cell and expedite its wide adoption on a commercial scale. Special attention is devoted to the performance and efficiency of PEMFC especially on vehicular application and key issues hindering further development of PEMFC to achieve its commercialization stage. Subsequently, various mitigation strategies proposed to address the aforementioned issues are outlined and discussed. Lastly, further research and development needs of the field are highlighted and discussed. Â© Springer Nature Singapore Pte Ltd. 2020.